Eslba Load Sharing Technique for Reputation Manager in Multiple Gateways - John Paul Antony, T; P. Victor, S (International Journal of Engineering and Technology, 2018)
Every node has the states of its neighbors such as Selfish, Unselfish and No Information state. The selfish node free path is constructed by avoiding selfish node in the route discovery process. Watch Dog mechanism helps to avoid such issues. Price and Reputation system (P&RS) helps to diminish the selfish nodes in a successful manner. Trustable node with low portability will go about as a Notoriety Manager and it keeps every one of the records of every node in a record system. The overload of RA leads to various problem and makes the communication very slow. In this paper we discuss about the RA affiliation and request in various possible ways. RA sends the affiliation to the nearest relay node to act as a RA for few nodes. Moreover we discuss the RA communication with Internet through Gateways and the load balancing algorithm – Energy Share Load Balancing Algorithm (ESLBA). The heap adjusting algorithm shares the heap between the nodes and channelizes the ideal course smarterly.